2018
DOI: 10.4103/jovr.jovr_21_17
|View full text |Cite
|
Sign up to set email alerts
|

Regression of giant olfactory groove meningioma and complete visual acuity recovery after discontinuation of cyproterone acetate

Abstract: Purpose:To report on the medical management of meningioma with compression of the optic chiasm associated with the use of cyproterone acetate (CA).Case Report:A 65-year-old woman who was being treated with CA presented with a recent decrease in visual function, leading to discovery of a giant olfactory groove meningioma with compression of the optic chiasm. CA was discontinued immediately, and her visual function improved dramatically. At 13 months, in addition to a significant improvement in visual and neuroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A strong association between cyproterone acetate (CA), a progesterone derivate and meningioma was rst reported in 2008 by Froelich et al [10], in a series of 9 patients with tumor regression after CA discontinuation. Since then, multiple similar reports have been published, and a clear relationship between meningioma and CA is now well established [11][12][13][14][15]. A recent study, based on the French national SNDS database, showed that women who initiated high dose CA treatment had a sevenfold increased risk of surgically treated meningioma with a strong dose-effect.…”
Section: Introductionmentioning
confidence: 93%
“…A strong association between cyproterone acetate (CA), a progesterone derivate and meningioma was rst reported in 2008 by Froelich et al [10], in a series of 9 patients with tumor regression after CA discontinuation. Since then, multiple similar reports have been published, and a clear relationship between meningioma and CA is now well established [11][12][13][14][15]. A recent study, based on the French national SNDS database, showed that women who initiated high dose CA treatment had a sevenfold increased risk of surgically treated meningioma with a strong dose-effect.…”
Section: Introductionmentioning
confidence: 93%
“…The suspicion of a link between CPA and meningiomaswas raised by our group in 2008[6]and was con rmedby numerous case seriesshowing regression or stabilization of meningioma(s) after CPA discontinuation [7,8,12,13,15,17,18,27,[29][30][31][32]. Gill et al [14]described an increased risk of meningioma(s)in patients under high dose CPA and with a longer than 1 year exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2009, following the results of our CPA studies [7,8,12,13,20,27], every patient presenting with a meningioma to our neurosurgical department was questioned about previous history of progestin treatment.Every newly diagnosed patient with intracranial tumor radiologically compatible with a meningioma associated with CPA intake, followed aconservative strategy starting with discontinuation of CPA and a close clinical and radiological follow-up.Surgery was onlyindicated in case of tumor growthon serial magnetic resonance imaging (MRI)or in severely symptomatic patients.…”
Section: Patients' Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature and a higher rate of multiple meningiomas suggest a strong relationship between this hormonal treatment and meningioma development. Therefore, delayed treatment of hormonal induced meningiomas with close clinical and MRI follow-up is recommended by several authors [3,8,9,13,19,22,23,26,28] in asymptomatic patients. Nevertheless, this management still needs further evaluation.…”
Section: Introductionmentioning
confidence: 99%